Screening of Maize Genotypes against Stalk Rot Disease in River Basin Area of Surkhet, Nepal - Magar, P.B.; Subedi, S.; Acharya, B.; Yadaw, R.B.; Pokhrel, K.R.; Dhakal, K. (Journal of Agriculture and Environment, 2020)
Stalk rot of maize (Zea mays L.) is becoming a serious threat in tropical and subtropical maize growing regions of Nepal. To identify the sources of disease resistance in maize genotypes, a field experiment was conducted under natural epiphytotic condition during the summer season of 2016 and 2017 with thirty genotypes in a randomized complete block design in two replications. Statistical analysis showed that percent disease incidence (PDI) and grain yield were highly significant among the tested genotypes. Most of the maize genotypes were resistant to moderately resistant, only few were susceptible in both years, indicating good sources of resistance in the available genotypes. During 2016, the highest PDI was found in Arun 4 (33.17%) followed by Rampur 27 (20.10%) and Arun 2 (20.06%) whereas TLBRS07F14 and TLBRS07F16 showed no disease incidence. Similarly, the highest and least grain yielders were identified as Rampur Hybrid 6 (6.77 t/ha) and Arun-4 (2.15 t/ha) respectively. In 2017, highest PDI was observed in Arun-2 (24%) followed by Arun-4 (22%) and no disease incidence was seen in TLBRS07F14. Highest grain yield was found in RAMS03F08 (7.38 t/ha) followed by Manakamana-3 (7.37 t/ha) and the lowest was recorded in Arun 4 (2.60 t/ha). These resistant genotypes can be utilized in national breeding program to develop stalk rot tolerant high yielding maize genotypes in future.